BIOMARKERS USED IN THE DETECTION OF INFECTIONS IN HORSES - Vezir, Busra; Matur, Erdal (Аграрний вісник Причорномор’я, 2026)
Early identification of infectious diseases in horses is crucial for accurate diagnosis, effective treatment, and improved clinical outcomes. However, distinguishing infectious conditions from non-infectious inflammatory processes remains challenging in equine practice due to overlapping clinical signs and nonspecific laboratory findings. Over recent years, a variety of hematological, biochemical, and acute phase biomarkers have been investigated to support the detection and monitoring of infections in horses. This article reviews the most commonly used biomarkers applied in equine infectious disease diagnostics, including white blood cell indices, neutrophil-to-lymphocyte ratio, serum amyloid A, fibrinogen, serum iron, haptoglobulin, CRP and Neutrophil Gelatinase–Associated Lipocalin (NGAL). The biological basis, diagnostic performance, and clinical relevance of these biomarkers are discussed, with particular emphasis on their roles in differentiating inflammatory responses, assessing disease severity, and monitoring treatment response. While acute phase proteins such as serum amyloid A and fibrinogen demonstrate high sensitivity to inflammatory stimuli, their limited specificity highlights the need for careful interpretation in conjunction with clinical findings and other laboratory parameters. Overall, current evidence suggests that no single biomarker is sufficient for the definitive diagnosis of infectious diseases in horses. Instead, a multimodal approach integrating clinical assessment with multiple biomarkers provides the most reliable diagnostic and prognostic information. Continued research is required to refine biomarker interpretation, establish standardized reference intervals, and improve their practical application in equine medicine.